“You should go so that others can come”: the role of facilities in determining an early departure after childbirth in Morogoro Region, Tanzania - McMahon-Rössle, Shannon A.; Mohan, Diwakar; LeFevre, Amnesty E.; Mosha, Idda; Mpembeni, Rose; Chase, Rachel P.; Baqui, Abdullah H.; Winch, Peter J. (BMC pregnancy and childbirth, 2015)
Tanzania is among ten countries that account for a majority of the world’s newborn deaths. However, data on time-to-discharge after facility delivery, receipt of postpartum messaging by time to discharge and women’s experiences in the time preceding discharge from a facility after childbirth are limited.
Gesehen am 10.06.2020